Metagovernance, political demand and policy advice: a case from Brazil. (4th July 2019) - Albert, Victor; Manwaring, Rob
ABSTRACT: There has been a call for a "second wave" of scholarship on policy advice to expand our understanding of the relational dynamics within a policy advisory system (PAS). In this article, we use a case from Brazil to address two key gaps in the PAS literature – the lack of attention to systems of network governance and the current predominance of "Westminster" empirical cases. To better understand the impact of policy advice within a system of networked governance, we apply the frame of "metagovernance" – the steering of governance networks. We then introduce and employ the concepts of funnelling, political brokering and gate-keeping to better understand how policy advice is shaped, modified and then either rejected or accepted. The contribution of the article is that, while much of the existing PAS literature describes the contours and key actors within an advisory system, we develop new conceptual scaffolding to better understand the trajectories and impact of policy advice, and the interplay between actors and agents, within a broader system of metagovernance.